Low-Temperature Technologies 2020
DOI: 10.5772/intechopen.89236
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nanoparticles on Performance Characteristics of Refrigeration Cycle

Abstract: Since few years, researchers are introduced nanorefrigerant in the recent development of refrigeration systems. This chapter briefly summarizes the behavior of different nanoparticles in vapor compression refrigeration cycle. The nanoparticles' infusion in refrigeration cycle affects the viscous behavior of the refrigerant. It is found that very limited studies have been done on viscosity characteristics of nanolubricants, but few reports states that viscosity increases with nanoparticles additive which improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…In comparison to other nanoparticles, carbon nanotubes are the best candidate for heat transfer enhancement of base refrigerants. The rate of heat transfer increases as the nanoparticle dimension reduces, while the pressure drop lowers as the nanoparticle dimension decreases [9].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison to other nanoparticles, carbon nanotubes are the best candidate for heat transfer enhancement of base refrigerants. The rate of heat transfer increases as the nanoparticle dimension reduces, while the pressure drop lowers as the nanoparticle dimension decreases [9].…”
Section: Introductionmentioning
confidence: 99%
“…The results also demonstrated a decrease in the viscosity of the lubricant when performing the viscosity test, which leads to a decrease in power consumption. A PH test was performed and it was found that an optimized compressor for cooling purposes was required [11]. The attempt to improve the performance of the compressive cooling system for the characteristics of heat transfer by adding ( AL2O3, R-134a, size 20 nanometers ) nano-cooling system was studied.…”
Section: Introductionmentioning
confidence: 99%
“…The use of nanofluids as nano-refrigerants has the potential to lead to smaller, more compact refrigeration systems which would require less compressor capacity, use less fuel, be more energy efficient and hence, more eco-friendly [18]. Silica NPs also have the potential to increase the solubility between the lubricant and the refrigerant, which would reduce wear and tear and increase the compressor life [19][20][21]. Hence, silica NPs, in this regard, have been found to display exceptional properties and have been touted for future use in refrigeration systems [22,23].…”
Section: Introductionmentioning
confidence: 99%